Types and Density of Microplastic in the Coastal Area of the Naras Hilir Village, Pariaman City, West Sumatera Province - Yolla, Yolla; M. Fauzi, M. Fauzi; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTMicroplastic is plastic pieces sized ≤ 5 mm. The presence of microplastic in sediment negatively affectsthe environment as well as the benthic organism. As the costal area of the Naras Hilir Village facing the Indian Ocean, the microplastics carried by the water may be stranded in the beach. A research aims to understand the type and density of microplastic present in the coastal area of the village has been conducted on May-July 2019. There were 3 stations, in  the intertidal zone,namely in the low tide, middle and high tide areas. In each station, 15 plots (50 x 50 cm) were placed. Sediment from each plot was scrapped 5 cm depth and then were sieved and microplastics were collected manually. Results shown that there were 4 types of microplastics, namely film, fragmen, foam and fiber. The density of microplastic was 13.24 item/m3. The most common microplasticpresent was film (4.44 item/m3).The highest microplasticdensity was in the high tide (6.49 item/m3), but there was no difference in microplastic densities in all sampling areas (p = 0.097 > 0.05). Keywords:Plastic Waste,Intertidal Zone, Coastal Sediment, Marine Debris